Life–Style and Behavioral Changes after COVID-19: A Perspective - Shirsath, Nitin Rajendra; Shitole, Rohit (Indian Journal of Pharmacy & Drug Studies, 2024)
Background and Aims: By May 18th 2020, India investigated 1 lakh infected cases from COVID-19, and as of 11th July 2020, the cases equaled 8 lakhs. Social distancing and lockdown rules were employed in India, which however had an additional impact on the economy, human living, and environment. Where a negative impact was observed on the economy and human life, the environment got a positive one. The impact of measures taken to contain COVID-19 on lifestyle-related behavior is undefined in the Indian population. Methods: The current study was undertaken to assess the impact of COVID-19 on lifestyle-related behaviors. An exploratory and anonymous general population-based Google survey was conducted among 1000 population. Herein, the data for the survey was collected through a well-structured questionnaire and the channel of data collection was Google forms. In brief, the study was conducted among the citizens of the Dhule district, North Maharashtra region, Maharashtra, India. Results: Based on the survey, the participants willingly participated in the study. The majority of participants have seen changes in their life after COVID-19. The participants gave priority in their life to both Family and Health and Connections and Wealth according to the survey. Many participants learn that we need to take mental health seriously to take care of ourselves and devote more time to ourselves. Conclusions: There have been too many changes are observed in human life style as a result of COVID-19.